Cartilage tissue engineering using a flow perfusion bioreactor - Silva, M. L Alves da (2008)
[Excerpt] Joint diseases include several conditions that have great impact on society, such as rheumatoid arthritis or osteoarthritis. Tissue engineering is one of the most promising alternatives to overcome the low capacity of cartilage self-repair in those debilitating diseases context. Chitosan-polybutylene succinate (C-PBS) scaffolds have been studied for their suitability for cartilage tissue engineering. Previous works have shown that these scaffolds support chondrocytes primary cultures, its growth and ECM production. C-PBS fiber meshes were produced by fiber extrusion, followed by hot compression, producing a 3D non-woven mesh of variable pore size. These fiber meshes were used for supporting human mesenchymal stem cells (hMSCs) chondrogenic differentiation. […]